Firestarter ebook - King, Stephen (2016)
Master storyteller Stephen King presents the classic #1 New York Times bestselling thriller, "his highest Fahrenheit reading yet" ( Time ). Andy McGee and Vicky Tomlinson were once college students looking to make some extra cash, volunteering as test subjects for an experiment orchestrated by the clandestine government organization known as the Shop. But the outcome unlocked exceptional latent psychic talents for the two of them—manifesting in even more terrifying ways when they fell in love and had a child. Their daughter, Charlie, has been gifted with the most extraordinary and uncontrollable power ever seen—pyrokinesis, the ability to create fire with her mind. Now the merciless agents of the Shop are in hot pursuit to apprehend this unexpected genetic anomaly for their own diabolical ends by any means necessary...including violent actions that may well ignite the entire world around them as Charlie retaliates with a fury of her own...